The Progressiveness of Islamic Financial Regulations In Encouraging The Growth of The Halal Ecosystem In The Digital Era - Hidayanto, Bani Idris; Gustanto, Edo Segara; Rahmawanti, Intan Nur (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2024)
The Islamic financial digitalization program is supported by several regulations both from laws and regulations, POJK No. 13/POJK.02/2018, Fatwa DSN-MUI No. 117 of 2008 concerning Technology-Based Financing Services based on Sharia Principles. This research applies a method in the form of literature research with a qualitative description approach. The purpose of this research can be used as a reference for the development of knowledge to comprehend the benefits of sharia economic law and as an effort to expand understanding related to the development of sharia financial regulations. The results of this research discussion is devided into two, the first one is that the development and progressivity of Islamic financial regulations in Indonesia is quite good, but still passive, the regulations which are less responsive in responding product developments in this digital era. Some regulations are still regulated in old regulations that have not shown digitalization in Islamic finance. Besides that, regulations are still spreading in various regulations and still no address for this subject matter specifically. The second, with the advancements in Islamic financial regulation, the halal ecosystem can thrive in the digital era. This will support the sustainable economic growth, the increase of financial inclusion, and provide Sharia-compliant financial solutions for an increasingly digitally connected global society.